2(x-y)-(x+y)

I have been stuck on this problem for ages.. Please help!!

6 answers

2(x-y)-(x+y)

2x - 2y - x - y = x - y
Oh!! Sorry; forgot to say what the objective is.. I'm supposed to simplify, but I'm not sure how to distribute the two and everything..
I still don't really understand.. Sorry....
Distribute over everything in the parentheses.

2(x - y) = 2x - 2y

-(x + y) = -x + -y = -x - y

2x - x - 2y - y = x - 3y
I still don't really understand.. Sorry....
Scratch that, I understand. Thank you!